Framing Mahasiswi Penghafal Al-Qur’an Terhadap Fenomena LGBT di Media Sosial - Ainun Jariah; Fina Dhiyaun Najihah; Sri Wahyuni; Sunaryanto (Program Studi Komunikasi dan Penyiaran Islam, STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2025)
This research aims to determine the views of female Quran-memorizing students regarding the LGBT phenomenon emerging on social media. The method used is qualitative research based on Robert M. Entman’s framing analysis, which consists of four dimensions: define problems, diagnose causes, make moral judgments, and treatment recommendations. The research informants are female students specializing in the study of the Quran and Exegesis (IAT) at STAI Dirosat Islamiyah Al-Hikmah Jakarta. The findings indicate that these students define the LGBT phenomenon on social media as a serious threat of normalizing deviance, triggered by unregulated algorithms, toxic social environments, and weak individual spiritual foundations. Morally, they evaluate this phenomenon as a form of extreme disobedience and a betrayal of human nature (fitrah) that is in absolute contradiction to Divine law. As a solution, they recommend a narrative counter-movement through massive Islamic educational content to challenge pro-LGBT campaigns in the digital space. Furthermore, technical measures such as content blocking by relevant authorities and Sharia-based sex education are deemed necessary to build the mental immunity of the younger generation.